Effects of electronic module intervention on teachers’ knowledge, beliefs and practices in drug abuse prevention among Balikpapan high school students, Indonesia - Ghozali (2019)
In spite of the widely campaign against drugs has been conducted, the problem of drug abuse stays at a very bothering level. In 2017, the number of drug abusers in Indonesia was 3,367,154 people or 1.77% of the population age 10-59 years, where East Kalimantan was ranked third out of 34 provinces with the prevalence of 2.12%. This study was aimed to develop and evaluate the effects of intervention using electronic module on teachers’ knowledge, beliefs, and practices in drug abuse prevention. An interventional study was conducted towards teachers in selected public junior high schools. A cluster random sampling was used to select schools in this study. A total of 260 teachers was involved in this study, 128 teachers in the group 1 and 132 teachers in group 2. Teachers’ knowledge, beliefs and practices of drug abuse prevention were measured using questionnaires at three times, baseline before intervention given, posttest 1 at one month after intervention and post-test 2 at six months after intervention. Electronic module of drug abuse was applied to group 1, while the usual printed one for group 2. Sociodemographic and baseline data were analyzed descriptively. Paired-t and Wilcoxon Test were used to analyzed effects of intervention towards teacher’s knowledge, beliefs and practices within group, while independent-t and Mann Whitney U Test were used to compare the effects between 2 groups. Effects of intervention between and within group then was analyzed using two-way repeated measures ANOVA. Knowledge, beliefs, and practices at six months after intervention were significantly higher rather than at baseline (P<0.05). There were no significant differences between groups in mean of knowledge and practices at six month after intervention (P>0.05), while the mean score of beliefs in electronic module group was significantly higher than printed module group (P<0.001). Within group comparison showed that electronic module significantly increased teachers’ beliefs and practices from baseline to one month and from one month to six month. The different condition for the knowledge, there was significant improvement from baseline to one month, but decreased from one month to six months. Printed module continuously increased teachers’ knowledge and practices but not for beliefs. There was significant increased of teachers’ beliefs from baseline to one month, but no significant changes from one month to six months. Based on consistency of results, educational intervention using electronic module was better than usual printed module in improving teachers’ beliefs, but not for teachers’ knowledge. Electronic and printed modules have the almost equal positive effect on teachers’ practices. Intervention using electronic module was significantly increased teachers’ knowledge, beliefs, and practices in drug abuse prevention.